Single Dose Antibiotic Prophylaxis in Lumbar Stenosis or Disc Surgery - Ali, Mohammed (Latakia University Journal -Medical Sciences Series, 2018)
We reviewed 60 patients (34 males and 26 females) who underwent single-level lumbar laminectomy and medial facetectomy for lumbar stenosis. Two grams of intravenous cefazolin was administered at the induction of general anesthesia. either in hospital or at home, additional antibiotic prophylaxis was not administered. The wounds were inspected on the first day after surgery,and on the 10th day after surgery at the sutures removal, and after 4 weeks. Results: Superficial wound redness was detected in 1 patient (1.6%), which improved with oral antibiotic, and 1 patient (1.6%) developed discitis which improved with nonsurgical management. None of the patients needed surgical re-exploration for infection or other complications. Conclusions: The current retrospective study proved that our antibiotic prophylaxis protocol is safe and efficacious. تقييم فعالية استخدام جرعة وحيدة من الصادات الحيوية في الوقاية من الانتانات في عمليات استئصال فتق النواة اللبية تمت دراسة 60 مريضا ( 34 ذكر , 26 أنثى ) أجري لهم استئصال فتق في النواة اللبية القطنية جراحيا . اعطي المرضى جرعة واحدة من الصادات الحيوية خلال فترة نصف ساعة قبل البدء بالتخدير مباشرة . تم استقصاء الجرح في اليوم الأول بعد الجراحة و في اليوم العاشر بعد الجراحة عند فك القطب و بعد شهرمن الجراحة . وكانت النتائج كما يلي : حدث انتان سطحي للجرح عند مريض واحد (1,6%) من المرضى و تحسنت حالته باستخدام الصاد الحيوي المناسب بالطريق الفموي. وعند مريض واحد آخر (1,6%) من المرضى تطور التهاب القرص بين الفقرات تحسن بالعلاج المحافظ النوعي, و لم يحتاج أي من المرضى إلى إعادة الفتح الجراحي بسبب الانتانات أو الاختلاطات. نستنتج أن استخدام صاد حيوي بجرعة وريدية وحيدة هو إجراء آمن و فعال للوقاية من الانتان بعد عمليات جراحة العمود القطني النظيفة , كما انه يوفر على المريض الكثير من الجهد والمال.